Sero-prevalence of visceral leishmaniasis (VL) among dogs in VL endemic areas of Mymensingh district, Bangladesh (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present study was conducted to determine the sero-prevalence of canine visceral leishmaniasis (VL) among street and owned dogs at Trishal Upazila of Mymensingh district, Bangladesh.Material and methods: Blood was collected asceptically from targeted dogs and serum was separated out using standard centrifugation method. The rK39-antigen-based dipstick test was used to detect anti-leishmania antibodies in serum.Results: The study revealed that 35% of the dogs in the study area were sero-positive for L. donovani. Living status of the dogs (street or owned) was a potential risk factor and sero-prevalence was significantly higher in free roaming street dogs (P=0.009)  and dogs with skin lesions and enlarged lymph nodes (P